2016
DOI: 10.7324/japs.2016.60424
|View full text |Cite
|
Sign up to set email alerts
|

Total Phenolics and Antioxidant Potentials of Rotula aquatica Lour

Abstract: Rotula aquatica Lour is a small branched shrub that grows characteristically among rocks and trailing over gravel in stream beds. It belongs to the family Boraginaceae and widely distributed throughout India. It is commonly called as Pasanabheda. The present study was aimed to evaluate the total phenolics and in vitro antioxidant activity in root and leaf extracts of Rotula aquatica Lour. The dried roots and leaves were subjected to soxhlet extraction utilizing chloroform and methanol followed by preliminary q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Correspondingly, Pallavi et al (2016) observed IC50 values of 91.65μg/ml and 81.98μg/ml in chloroform and methanol extracts of Rotula aquatica roots respectively and IC50 of 99.90 μg/ml and 87.65μg/ml in the leaves extract. Nitric oxide is a diffusible free radical that react with superoxide anion and form potential cytotoxic molecule such as peroxynitrite.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Correspondingly, Pallavi et al (2016) observed IC50 values of 91.65μg/ml and 81.98μg/ml in chloroform and methanol extracts of Rotula aquatica roots respectively and IC50 of 99.90 μg/ml and 87.65μg/ml in the leaves extract. Nitric oxide is a diffusible free radical that react with superoxide anion and form potential cytotoxic molecule such as peroxynitrite.…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, total flavonoid content was found to be 2.60 g and 1.79 g quercetin equivalent/100 g methanolic and aqueous extract respectively of R. aquatic (Pallavi et al, 2016). Hidalgo et al (2010) have reported that flavonoid synergistically interact with free radicals to neutralize them.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations